2021
DOI: 10.1002/cac2.12191
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor‐low breast cancer: Biology chaos and treatment paradox

Abstract: Hormone receptor testing mainly serves the purpose of guiding treatment choices for breast cancer patients. Patients with estrogen receptor (ER)-positive breast cancers show significant response to endocrine therapy. However, the methods to define ER status and eligibility for treatment remain controversial. Despite recent guidelines considering staining ≥1% of tumor nuclei by immunohistology as ER-positive, it has raised concerns on the benefit of endocrine therapy for tumors with ER 1%-10% expression, termed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 81 publications
2
30
0
Order By: Relevance
“…It seems that the dichotomous ER status (as negative or positive) limited predictive and prognostic values, and ER-low positive status might provide additional information among ER-positive patients. 6 Cancer May 1, 2022…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the dichotomous ER status (as negative or positive) limited predictive and prognostic values, and ER-low positive status might provide additional information among ER-positive patients. 6 Cancer May 1, 2022…”
Section: Introductionmentioning
confidence: 99%
“…Currently, different multigene tools (such as 21‐gene and 70‐gene panels) have been developed to stratify patients with early, ER‐positive, human epidermal receptor 2 (HER2)‐negative breast cancer into different risk groups to guide the use of chemotherapy. It seems that the dichotomous ER status (as negative or positive) limited predictive and prognostic values, and ER‐low positive status might provide additional information among ER‐positive patients 6 …”
Section: Introductionmentioning
confidence: 99%
“…Endocrine therapy remains to be the first choice for the first line treatment of luminal type MBC patients, both in guidelines and clinical practice [ 22 , 23 ]. However, among patients with a low ER expression, endocrine therapy seems to be less effective [ 15 ]. Traditionally, we tend not to use combined treatment of ET and CT because of the antagonism of chemotherapy-induced cytotoxicity by antiestrogens [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed the opposite results, which further demonstrated that patients with ER heterogeneity had a completely different biological behavior and treatment response from ER positive patients. On the other hand, besides the fact that ET is not suitable for ER/PR negative patients, researchers also found that patients with a ER low expression had worse treatment outcomes for ET and overall survival compared with a ER high expression [ 15 ]. This phenomenon, to some extent, suggests that patients with ER heterogeneity might be similar to those with a low ER expression or negative ER expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation